Role of entrepreneurial orientation in developing entrepreneurial competencies: contingent influence of environmental turbulence / Muhammad Hanif ... [et al.] - Hanif, Muhammad; Abdul Rahim, Mohammad Zulkifli; Qureshi, Imran Munawar; Abd Halim, Mutia Sobihah; Aftab, Muhammad (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2024)
Entrepreneurship has an integral role in the development of the country’s economy. In achieving firm success, the role of entrepreneurial orientation (EO) and entrepreneurial competencies (EC) is an important mechanism to explore. In this study, a model was developed to examine the consequential influence of EO on ECs and environmental turbulence (ET) as a moderator. The population of the study were entrepreneurs from different industries in Pakistan. Based on the Resource-Based view (RBV) and Giessen Amsterdam Model (GAM), a survey of 600 entrepreneurs was conducted to collect data and 422 valid responses were analyzed using Jeffrey’s Amazing Statistics Program (JASP). Results suggest a significant influence of EO on EC. ET also has a significant moderating role on the aforementioned relationship. Further, this study concluded that in times of higher ET, firms with an EO have a good chance of survival. In this respect, entrepreneurs are advised to develop and maintain an EO. Policy makers are encouraged to provide support to entrepreneurs during times of high environmental turbulence. Future studies can look at the role of market orientation on EC, as further explore the role of ET